Development and validation of a nutrition assessment questionnaire based on the social and behavior change model for adolescents in Ethiopia - Fantahun Ayenew Mekonnen; Gashaw Andargie Biks; Telake Azale; Netsanet Worku Mengistu (Frontiers in Public Health)
BackgroundA reliable assessment of behavior change requires the use of a validated tool based on an appropriate behavior change model. Research on tools for assessing nutrition behavior change is limited.ObjectiveThis study aimed to develop and validate a questionnaire for assessing plant-protein food consumption behaviors based on Pender’s behavior change model, specifically for adolescent girls in Ethiopia.MethodsA collection of items was generated by examining relevant behavior change theories and manuals, dietary guidelines, and literature focused on pulses’ food function, processing, and preparation. The items were examined for content and face validity. Exploratory factor analysis was performed after verifying its assumptions, such as the factorability of the instrument using Bartlett’s test of sphericity and Kaiser-Meyer-Olkin (KMO) measure of sampling adequacy. Eigenvalue and scree plot were used to determine the number of factors. Factor loadings and communalities were employed for item retention. Cronbach’s alpha was calculated to assess the reliability at the scale and dimension levels.ResultsOf the 53 items analyzed, 29 items and 6 factors were retained. The overall scale-level reliability was measured at 0.7210, while the factor-level reliabilities were as follows: 0.69 for factor 1 (i48, i49, i50, i52, i53, i31, and i32), 0.67 for factor 2 (i7, i8, i9, i10, i12, i13, and i14), 0.63 for factor 3 (i23, i24, i25, i26, fi27, and i28), 0.31 for factor 4 (i4, i5, i40), 0.59 for factor 5 (i35, i36, and i37), and 0.58 for factor 6 (i18, i19, and i20).ConclusionThe tool has an acceptable scale-level reliability. The factors are theoretically meaningful and align with the recommendations. The tool can serve as a foundation for developing tools in related fields. However, it requires further refinement before it can be used as a standard tool.